Does ESG Disclosure or Size Which Matters to Profitability? Case of Banking Companies Listed on The Indonesian Capital Market - Pranaja, Yuri; Ossi Ferli; Insan Fajri Ibrahim; Febi Saynauli Simanjuntak (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
This study aims to analyze the effect of Environmental, Social, and Governance (ESG) Disclosure on the financial performance of banking companies listed on the Indonesia Stock Exchange for the period 2019–2023. This study uses a quantitative approach with the panel data regression method and the Random Effect Model (REM) model, and involves 14 banking companies that meet the ESG data criteria based on GRI standards. The dependent variables used are Return on Assets (ROA) and Return on Equity (ROE), while the independent variables consist of the combined ESG score and each component E, S, and G, with company size and leverage as control variables. The results of the study show that simultaneously ESG disclosure does not have a significant effect on ROA or ROE. However, partially, only the environmental component (E) shows a positive and significant effect on ROE. In contrast, the social and governance components do not show a significant effect. In addition, company size is proven to have a positive effect on financial performance, while leverage does not have a significant effect. These findings indicate that ESG has not fully become a determining factor in the financial performance of banking in Indonesia.